Water Distribution and the Impact of Relative Humidity in a PEMFC Energy System using Macroscopic Energy Representation by Inversion Control - Farid Saadaoui; Khaled Mammar; Abdaldjabar Hazzab (Majlesi Journal of Electrical Engineering)
One of the most significant handicaps and disadvantages for the proper operation of the polymer membrane in a PEMFC fuel cell energy system is the distribution of water. In this paper, we propose a mathematical model for defining the static and dynamic characteristics of energy behaviour (voltage, electricity, and relative humidity) for various input operating parameters (hydrogen, oxygen, water flow rates, temperature and current). This energy phenomenon is used in a wide range of operating conditions to ensure the exploitation of the energy produced, which will be modeled by a recent practicable and achievable graphical formalism, the Macroscopic Energy Representation (MER), which is used because of its simplicity which feasibility, and is based on the action/reaction principle and controlled by a simple inversion method. This behavior is designed to deduce and recommend an energy management plan for the PEMFC system that takes into account the various states of flooding and drought and contributes to an optimal humidity level for the system's implementation. The simulation results show that to operate correctly for this model, the Relative Humidity must be in the neighborhood of 100% for the device to be effective.